PELAKSANAAN SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PENDIDIKAN AGAMA ISLAM DI SMA IT AS - SAKINAH TANJUNGPINANG TAHUN PELAJARAN 2023/2024 - Septy Hermina (UNISAN JURNAL, 2024)
The aim of this research is to examine how learning supervision is carried out by the director and teachers at As-Sakinah Tanjungpinang IT High School, which includes understanding: How is supervision carried out by the director to improve teaching performance at As-Sakinah Tanjungpinang IT High School? What are elementary schools doing to improve the performance of Islamic religious education teachers at SMA IT As - Sakinah Tanjungpinang South Lampung. What are the Director’s limitations in improving the performance of Islamic religious education teachers at SMA IT As-Sakinah Tanjungpinang? Research findings include the following: Principal supervision is planned systematically, continuously, and based on an agreement between the principal and teachers. At the observation stage, the principal’s activities did not interfere with students’ learning in class, and at the end of the lesson he encouraged students to study actively. The results of the supervision stage are discussed together by the teacher and principal who also discuss the teacher’s weaknesses in the classroom with the hope that the teacher can overcome them in the future. The educational process is served well by teachers, as evidenced by the planning of lesson plans that meet the criteria outlined in the teacher performance standards. In addition, at the learning implementation stage, a teacher can effectively master the subject matter by using various teaching methods and then use these methods to learn.